Statistical Methods for Controlling the Quality of Crude Oil Products in Iraq - Hussain Jawad, Ethar (Journal of Economics and Administrative Sciences, 2023)
The purpose of this study is to measure the levels of quality control for some crude oil products in Iraqi refineries, and how they are close to the international standards, through the application of statistical methods in quality control of oil products in Iraqi refineries. Where the answers of the study sample were applied to a group of Iraqi refinery employees (Al-Dora refinery, Al-Nasiriyah refinery, and Al-Basra refinery) on the principles of quality management control, and according to the different personal characteristics (gender, age, academic qualification, number of years of experience, job level). In order to achieve the objectives of the study, a questionnaire that included (12) items, in order to collect preliminary information about the study sample was designed. The data was analyzed statistically and hypotheses were tested using the SPSS statistical package. The study relied on a random sample of 225 individuals, of which 205 were valid. The most important results obtained are: The degree of applying control over quality management in the refineries under study was: 68.8% for the principle of senior management's commitment to quality, 65.2%  for the principle of planning for the application of quality standards, and 65.% for the principle of strengthening the culture of quality among workers. The level of quality of some crude oil products in the refineries under study was estimated at 45%. In addition to the existence of a statistically significant correlation between the application of the principles of control over quality management and the quality of some oil products.